Cover crop effects on the soil microbiome and microbially mediated soil functions - Yerlan, Arsen, author; Schipanski, Meagan, advisor; Wrighton, Kelly, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2024)
Cover crops are often grown to improve soil health through changes in soil physical, chemical, and biological properties. Currently, there is growing interest in identifying how soil microbes may mediate some of the benefits provided by cover crops. However, most studies analyzing cover crop effects on the soil microbiome and soil health have been conducted in controlled settings such as greenhouses for short-term effects and field studies have focused on accumulated, longer-term effects. We conducted a short-term field experiment in northern Colorado with four different cover crop species: cereal rye (Secale cereale), hairy vetch (Vicia villosa) rape seed (Brassica napus), and sorghum (Sorghum bicolor) planted in August 2022 as monocultures and a no cover crop control to research these effects within a field environment at the time of cover crop termination in May 2023 and into the subsequent maize cash crop. During the respective seasons, cover crop and maize shoot biomass and bulk and rhizosphere soil were sampled. Soil samples were analyzed for soil extracellular enzymes L-leucine aminopeptidase (LAP), β-1,4-N-acetyl-glucosaminidase (NAG), β-glucosidase (BG), and acid phosphatase (PHOS); dissolved organic carbon concentrations (DOC); inorganic nitrogen concentrations; and soil aggregate stability. Only rhizosphere soil was used for soil microbiome analyses. Of all the cover crops, cereal rye and hairy vetch accumulated the most shoot biomass but did not differ from each other, and maize shoot biomass did not differ across treatments. Prior to cover crop termination in the spring, only rape seed stimulated LAP enzyme production compared to the control. Rape seed and cereal rye treatments had greater DOC concentrations than sorghum, and bulk soil DOC concentrations were greater than the rhizosphere. Inorganic nitrogen concentrations were lowest in cover crops that accumulated the most shoot biomass, i.e. cereal rye and hairy vetch. Soil aggregate sizes increased under living cereal rye relative to the control. Cover crops had several legacy effects that persisted into the maize crop, but these were not consistent with the effects found prior to termination: cereal rye stimulated BG and PHOS activity compared to sorghum. BG enzyme activity and DOC concentrations were greater in bulk soil compared to rhizosphere under the maize crop. Despite finding differences in cover crop effects on soil properties, we found no differences in microbial diversity indices or structure. However, under living cereal rye, one organism classified as genus Massilia was found to be enriched compared to the control but did not correlate with any measured soil functions. We were able to match our 16S BLAST results with a database to match with 15 MAGs at >97%. Our research confirms findings from studies performed in controlled settings that within a single season cover crops can modify the soil microbiome at an organismal level and influence soil functions, and our results suggest that frameworks built to describe soil microbiome and soil health dynamics are also applicable to the field. We also show that 16S taxonomic results may soon be useful in proposing potential microbial function, given that such MAG databases continue to be improved. Overall, this research contributes to the linking the soil microbiome with cover cropping and soil health, with further implications likely being microbiome management for sustainable agriculture.